IMPLEMENTASI SOFTWARE HEC-RAS 4.1.0 DAN EPA STORM WATER MANAGEMENT MODEL (SWMM) 5.1.0 PADA EFEKTIVITAS ANALISIS SALURAN DRAINASE (STUDI KASUS DESA KELET KECAMATAN KELING KABUPATEN JEPARA) - Efrizal, Ersa; Adi Saputro, Yayan; Hidayati, Nor (Civil Engineering of Universitas Islam Nahdlatul Ulama Jepara, 2022)
In the area of highway Kelet - Bangsri area, Kelet Village, drainage problems and flooding often occur along the highway during the rainy season. From the problems found that there are no drainage channels as a result of residential construction that does not pay attention to the drainage function and can result in damage to road construction. This final project analyzes drainage channels with the aim of knowing alternative flood management. The results of the hydrological planning calculations will be used as the basis for hydraulic analysis, rainfall calculations using the isohyet method. The hydraulics analysis was carried out using the HEC-RAS and EPA SWMM programs. Based on the results of the analysis of existing conditions, it was found that inundation occurs because the capacity of the channel is not able to drain the flood discharge, such as the dimensions of the channel that are not suitable so that new planning is needed. The results of the analysis of the EPA SWMM software are more effective to be used as an alternative for handling the right flood problem according to the condition of the Kelet - Bangsri Highway, Kelet Village, Keling District, Jepara Regency with the planning of the new drainage channel dimensions of B = 0.6m and H = 0.8m.